PENCITRAAN KEISLAMAN DALAM FILM AYAT-AYATCINTA - Hermawan, Herry (Universitas Prof. Dr. Moestopo (Beragama), 2010)
This research is concerned with the social construction of islamic simbolization reality on films and with the fac tors that constitute this reality. Through the qualitative research method, the analysis techniques in use were genre and narrative analysis, and hermeneutics analysis.Based on research, social construction of islamic simbolization reality on film is a reflection of society attitudeswhich create the polarization have a cultural context. In this sense, film, in the context of social construction of reality, is an arena of ideas and beliefs people have are systematically related to actual, spiritual and material conditions of existence.The result of this research showed that islamic simbolization reality whether it is constructed by society or by film derive from the paramount realities of interaction between religion and culture.